A Novel Mechanism of Preferential Enrichment Phenomenon Observed for the Cocrystal of (RS)‐2‐{4‐[(4‐Chlorophenoxy)methyl]phenoxy}propionic Acid and Isonicotinamide. Issue 71 (22nd November 2019) - Takahashi, Hiroki; Numao, Yuki; Motokawa, Junko; Clevers, Simon; Coquerel, Gérard; Tsue, Hirohito; Tamura, Rui
Abstract: A new entry of chiral anti‐hyperlipoproteinemia drug is reported, showing an excellent preferential enrichment (PE) phenomenon which is not caused by a polymorphic transition during crystallization, but is proposed to occur by a novel mechanism involving partially irregular stacking of R and S homochiral two‐dimensional (2D) sheets with a large dipole moment, followed by selective redissolution of one homochiral 2D sheet into the mother liquor during crystallization. The cocrystal composed of ( RS )‐2‐{4‐[(4‐chlorophenoxy)methyl]phenoxy}propionic acid (CPPPA) and achiral isonicotinamide exhibited a substantial enrichment in the mother liquor up to 93 % ee by simply repeating recrystallization under nonequilibrium conditions using high supersaturation. Furthermore, the deposited crystals with low ee values obtained at the end of PE experiment were second harmonic generation (SHG)‐positive, indicating the formation of homochiral domains in the deposited crystals, which reflects the proposed mechanism of PE. Abstract : Spontaneous resolution : The cocrystal consisting of racemic anti‐hyperlipoproteinemia drug (CPPPA) and achiral isonicotinamide (INA) exhibited a substantial enantiomeric enrichment in the mother liquor up to 93 % ee by simple recrystallization under nonequilibrium conditions using high supersaturation in 2‐PrOH at 20 °C.